Studies on Transportation of Fish I Packaging of Frozen Fish in Insulated Containers - PERIGREEN, A. (Fishery Technology, 1968)
The paper deals with certain technological aspects oftransportation of fish. Frozen fish packed in thermocole insulatedplywood box (tea chests) and transported has been found to remainin good condition, for 3 to 4 days. Fish reaching the destination in athawed state can be stored in crushed ice for a further period of 2-3days. The effect of initial temperature of frozen fish on the storagelife, the maximum storage period for different types of frozen fishpacked in the insulated container and the changes in chemical andorganoleptic qualities of different varieties of fish under conditionof transport are also discussed.